Association Between the Autonomy of Peruvian Women and the Choice of the Place of Delivery: Analysis of a National Survey, 2019 - Cueva, Gerald Alexander Hernandez (2023)
Objectives: To determine the association between Peruvian women’s autonomy and place of delivery. Methods: An analytical cross-sectional study of secondary data from the Demographic and Family Health Survey 2019 was carried out. The dependent variable was institutionalized childbirth, and the independent variable was women’s autonomy. Likewise, the association between women’s autonomy and institutionalized childbirth was evaluated using Poisson family generalized linear models with logarithmic link function, and crude (PR) and adjusted prevalence ratios (aPR) with their respective 95% confidence interval (CI) were estimated. Results: The analysis included 15,334 women aged 15–49 years. It was found that a high proportion of women had a low level of autonomy (42.6%; 95% CI: 41.5–43.7), while 92.1% (95% CI: 91.3–92.9) had institutionalized childbirth. Moderate (PR: 1.10; 95% CI: 1.08–1.12) and high (PR: 1.13; 95% CI: 1.12–1.15) levels of women’s autonomy were found to be associated with institutionalized childbirth, and the same association was found in the adjusted analysis. Conclusion: Being a woman with a higher level of autonomy was related to a higher prevalence of institutionalized childbirth. Therefore, as decision-making is a multifactorial characteristic, it is necessary to study in depth the determinants of non-institutionalized childbirth in women with less autonomy.